Interactions between Respiratory, Cardiac and Stepping Rhythms in Decerebrated Cats: Functional Hierarchical Structures of Biological Oscillators - Kawahara, K.; Yamauchi, Y.; Niizeki, K.; Yoshioka, T. (Methods of Information in Medicine, 1994)
Interactions are described of central origin between respiratory, cardiac and stepping rhythms during fictive locomotion in paralyzed, vagotomized, and decerebrated cats. Fictive locomotion was induced by tonic electrical stimulation of the mesencephalic locomotor region (MLR). The coherence between heart beat fluctuation, the efferent discharges of the phrenic, and the lateral gastrocnemius nerves was used to evaluate the strength of the coupling between those three rhythms. The heart beat rhythm was modulated by the centrally generated respiratory and stepping rhythms. The central respiratory rhythm was modulated by the centrally generated stepping rhythm. Based on the present findings, we have proposed a new model concerning the functional hierarchical structures of the three biological oscillators.
Keywords: Fictive Locomotion; Fictive Respiration; Central Pattern Generators; Coherence function